Marketisasi Agama di Ruang Virtual YouTube: Perspektif Teo-Antropologi Digital - Henderikus Nayuf (Institut Agama Kristen Negeri Toraja, 2026)
This research focuses on the phenomenon of the marketization of religion in virtual spaces, specifically on the YouTube platform. Amidst technological disruption and massive digital penetration, religious teaching has experienced disruption in its teaching methods. Technological developments have created new spaces for the production, dissemination, and consumption of religious teaching. The YouTube platform is one such virtual space that presents a transformation in religious teaching through a variety of engaging and contextual religious content. Religion then finds itself in an arena of contestation, which is then packaged with a market approach. Using a netnographic approach, this research aims to analyze the phenomenon of the marketization of religion from the perspectives of theology and digital anthropology. The theological approach helps us understand the implications of using the YouTube platform as an instrument for religious teaching through the commodification of symbolic messages. Meanwhile, anthropology guides us to understand the interaction between humans and technology. The results of this study indicate that the marketization of religion in virtual spaces, particularly on the YouTube platform, has been influenced by technological disruption with the power of algorithms shaped by the global market. Another finding is that religious leaders experience personal branding driven by market preferences, which has the potential to shift the sanctity and authority of religion. Fokus penelitian ini adalah fenomena marketisasi agama di ruang virtual, secara khusus pada platform YouTube. Di tengah disrupsi teknologi dengan penetrasi digital yang masif, pengajaran agama mengalami disrupsi dalam metode pengajarannya. Perkembangan teknologi menghadirkan ruang baru bagi produksi, penyebaran dan konsumsi pengajaran agama. Platform YouTube merupakan salah satu ruang virtual yang menghadirkan tranformasi pengajaran agama melalui beragama konten agama yang menarik dan kontekstual. Agama kemudian berada pada arena kontestasi yang kemudian dikemas dengan pendekatan market. Dengan menggunakan pendekatan netnografi, Penelitian ini bertujuan untuk menganalisa fenomena marketisasi agama dengan perspektif teologi dan antropologi digital. Pendekatan teologi menolong kita untuk memaknai implikasi dari pemanfaatan platform YouTube sebagai instrumen pengajaran agama melalui komodifikasi pesan simbolik. Sementara antropologi mengarahkan kita untuk memahami proses interaksi antara manusia dan teknologi. Hasil penelitian ini menunjukkan bahwa marketisasi agama di ruang virtual, khususnya platform YouTube telah dipengaruhi oleh disrupsi teknologi dengan kekuatan algoritma yang dibentuk oleh pasar global. Temuan lainnya adalah para pemuka agama mengalami personal branding yang dikehendaki oleh selera pasar yang berpeluang menggeser kesakralan dan otoritas agama.